Effects of an Intravenous Infusion of Emulsified Fish Oil Rich in Long-Chained Omega-3 Fatty Acids on Plasma Total Fatty Acids Profile, Metabolic Conditions, and Performances of Postpartum Dairy Cows During the Early Lactation - Mezzetti, Matteo; Piccioli-Cappelli, Fiorenzo; Minuti, Andrea; Trevisi, Erminio (Frontiers in Veterinary Science, 2022)
A group of 10 multiparous Italian Holstein cows were housed in individual tied stalls and infused with 150 ml of saline (CTR; 5 cows), or of 10% solution rich in long-chained omega-3 fatty acids (n3FA; 5 cows) at 12, 24, and 48 h after calving. From −7 to 21 days from calving (DFC), the body condition score, body weight, dry matter intake (DMI), and milk yield were measured, blood samples were collected to assess the plasma fatty acids (FA) and metabolic profiles, and milk samples were collected to assess the milk composition. Data underwent a mixed model for repeated measurements, including the treatment and time and their interactions as fixed effects. Plasma FA profile from n3FA cows had lower myristic and higher myristoleic proportions, higher cis-11,14-eicosadienoic acid and monounsaturated FA proportions at 3 DFC, and lower cis-10-pentadecanoic proportion at 10 DFC. Besides these, n3FA cows had higher eicosapentaenoic (EPA) and docosahexaenoic (DHA) proportions (1.09 vs. 0.71 and 0.33 vs. 0.08 g/100 g), confirming the effectiveness of the infusion in elevating plasma availability of these FA. The plasma metabolic profile from n3FA cows revealed a tendency toward a lower concentration of reactive oxygen metabolites at 1 DFC and lower haptoglobin at 2 and 3 DFC, reflecting a mitigated inflammatory state. Furthermore, n3FA cows had a higher DMI during the first week of lactation. Higher DMI of n3FA could account for the changes detected on their plasma FAs, the higher milk yield they had at 1 and 2 DFC, the reduced lactose and urea nitrogen content in their milk. Higher DMI could also account for the lower plasma urea that n3FA cows had at 1 and 2 DFC, suggesting a lower amount of endogenous amino acids deserved to gluconeogenic fate. Milk from n3FA cows had lower rennet clotting time and higher curd firmness, which is probably driven by a higher EPA and DHA inclusion in the milk fat. Together, these outcomes suggest that the infusion exerts a short-term anti-inflammatory action on dairy cows at the onset of lactation.